Using Project-Based Learning in Enhancing Students' Speaking Skill at SMA PSKD 7 - Kaunang, Chrisce Juonata (JET (Journal of English Teaching), 2017)
AbstractThe objectives of this research were to improve the students’ speaking skill and students’ interest about learning speaking by using Project-based learning. This research used classroom action research method in which the subject was the 25 ten graders of SMA PSKD 7 Depok and the subjects consisted thirteen males and twelve females. The quantitative data were analyzed by computing the students’ score of pre-test, post-test 1, and post-test2. Based on the data results, the mean score of pre-test, post-test in Cycle1, and post-test Cycle2 were respectively 49.12, 66.4, and 70.08. The gain of pre-test to post-test1 was 35.17%, the gain of post-test1in cycle 1 to post-test cycle 2 was 6.14%, and from the pre-test to post-test 2 in cycle 2 was 43.48%. The qualitative data were described based on interview and field-note to the improvement of students’ speaking skill. The findings showed that Project-based learning could improve the students’ speaking skill, it is suggested to use this method in teaching speaking skill. Keywords: CAR, Project-based learning